Ask Question
28 March, 19:33

7x+3 (-x+6) = 42 Show all steps and properties used

+5
Answers (1)
  1. 28 March, 21:27
    0
    45/34

    Step-by-step explanation:

    7x+3 (-x+6) = 42

    7x (-x+6) = 42+3=45

    -8x + 42x=45

    34x=45

    x=45/34
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “7x+3 (-x+6) = 42 Show all steps and properties used ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers